2012
DOI: 10.1097/aln.0b013e318255e550
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Blood and Blood Component Utilization as Assessed by an Anesthesia Information Management System

Abstract: The use of data acquired from an anesthesia information management system allowed a detailed analysis of blood component utilization, which revealed significant variation among surgical services and surgical procedures, and among individual anesthesiologists and surgeons compared with their peers. Incorporating these methods of data acquisition and analysis into a blood management program could reduce unnecessary transfusions, an outcome that may increase patient safety and reduce costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
137
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 36 publications
2
137
1
1
Order By: Relevance
“…Secondly, increasing evidence suggests that over-transfusion of allogeneic blood products is associated with increased morbidity and mortality due to infectious, immunological, pulmonary, and thromboembolic complications [5,6,7,8]. Especially worrisome is the substantial inter-institutional variability of transfusion practice, implicating high levels of insecurity regarding the indication for hemotherapy and potentially inappropriate usage [9,10]. Furthermore, it appears odd that hemoglobin levels of critically ill patients on intensive care units show a convergence over time, irrespective of the admitting hemoglobin level, age, and comorbidities [11].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, increasing evidence suggests that over-transfusion of allogeneic blood products is associated with increased morbidity and mortality due to infectious, immunological, pulmonary, and thromboembolic complications [5,6,7,8]. Especially worrisome is the substantial inter-institutional variability of transfusion practice, implicating high levels of insecurity regarding the indication for hemotherapy and potentially inappropriate usage [9,10]. Furthermore, it appears odd that hemoglobin levels of critically ill patients on intensive care units show a convergence over time, irrespective of the admitting hemoglobin level, age, and comorbidities [11].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of EHRs implicitly promised advanced data analytics to improve patient care and prevent unnecessary treatment [68]. The use of EHR systems [70,71,76,77] has enabled tailored feedback to the provider at the critical time of order entry to promote appropriate use [72,[78][79][80][81]. While several studies have shown beneficial impacts of CDS, large meta-analyses have failed to show a mortality benefit or meaningful impacts in reducing length of stay, adverse events, or costs [82][83][84][85].…”
Section: How Is Cds Effective?mentioning
confidence: 99%
“…[1][2][3] Although transfusion can be lifesaving in some clinical scenarios, most observational studies have shown a clear relationship between transfusion and adverse outcomes. [4][5][6][7] In prospective clinical trials that have compared liberal to restrictive transfusion strategies, the findings have revealed either no benefit [8][9][10][11][12] or increased morbidity and mortality 13 associated with increased use of transfusions.…”
Section: Introductionmentioning
confidence: 99%